Pemetaan Partisipatif Wisata Grojogan Watu Purbo sebagai Destinasi Wisata Berkelanjutan - Sekarsih, Fitria Nuraini; Arsanti, Vidyana; Wahyuningtyas, Puji; Arfianto, Septian Dwi; Kukuh, Kukuh; Madani, Erika Nurhanifa (Universitas Muhammadiyah Mataram, 2025)
Abstract: The activity “Participatory Mapping of Grojogan Watu Purbo Tourism” aims to support the structuring and development of Grojogan Watu Purbo tourist destination to become a sustainable nature tourism. Grojogan Watu Purbo, which is located in Bangunrejo Hamlet, Merdikorejo Village, Sleman, has great natural potential, but still needs further structuring so that its attractiveness and management are optimal. This activity was carried out by the Geography Study Program Lecturer Team and 2022 students through several stages, namely: (1) education and socialization to the community about the importance of protecting the environment and sustainable tourism management, (2) mapping the area using drone technology and Geographic Information Systems (GIS), and (3) making maps and tourism profile videos. Efforts to realize sustainable tourism in Grojogan Watu Purbo Tourism through education, socialization, and area mapping with drone technology and Geographic Information Systems (GIS) make a real contribution to the planning and management of tourist areas. Outputs in the form of maps, profile videos, and publications on social media not only function as a means of promotion, but also as a strategic tool in making decisions on area development. The resulting map helps managers in planning environmentally friendly infrastructure and as a basis for analyzing the impact of tourist visits. Abstrak: Kegiatan “Pemetaan Partisipatif Wisata Grojogan Watu Purbo” bertujuan untuk mendukung penataan dan pengembangan destinasi wisata Grojogan Watu Purbo agar menjadi wisata alam yang berkelanjutan. Grojogan Watu Purbo yang terletak di Dusun Bangunrejo, Desa Merdikorejo, Sleman, memiliki potensi alam yang besar, namun masih memerlukan penataan lebih lanjut agar daya tarik dan pengelolaannya optimal. Kegiatan ini dilaksanakan oleh Tim Dosen Program Studi Geografi bersama mahasiswa angkatan 2022 melalui beberapa tahapan, yaitu: (1) edukasi dan sosialisasi kepada masyarakat tentang pentingnya menjaga lingkungan dan pengelolaan wisata secara berkelanjutan, (2) pemetaan wilayah menggunakan teknologi drone dan Sistem Informasi Geografis (SIG), serta (3) pembuatan peta dan video profil wisata. Upaya mewujudkan pariwisata berkelanjutan di Wisata Grojogan Watu Purbo melalui edukasi, sosialisasi, dan pemetaan wilayah dengan teknologi drone serta Sistem Informasi Geografis (SIG) memberikan kontribusi nyata dalam perencanaan dan pengelolaan kawasan wisata. Luaran berupa peta, video profil, dan publikasi di media sosial tidak hanya berfungsi sebagai sarana promosi, tetapi juga sebagai alat strategis dalam pengambilan keputusan pengembangan kawasan. Peta yang dihasilkan membantu pengelola dalam merencanakan infrastruktur yang ramah lingkungan serta sebagai dasar analisis dampak kunjungan wisatawan.